The Reception of John Locke’s Writings at Christ Church, Oxford, c. 1690–1800 - Chatterjee, Jacob Donald (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2023)
This article presents some overlooked evidence on the reception of John Locke’s writings at Christ Church, Oxford. It is intended to supplement a new article in the History of Universities on the surprisingly positive response to Locke’s Essay Concerning Human Understanding (1689) at that bastion of late seventeenth-century high churchmanship. This evidence sheds new light on: the reception of Epicureanism at that college in the 1650s; Locke’s personal connections at Christ Church; book-holdings of Locke’s writings at the early eighteenth-century college; some unnoticed uses of Locke’s writings by members of Christ Church; the European and North American reception of one Christ Church Lockean; and, the changing trajectory of the later eighteenth-century reception of Locke at that college.